Comparison of proton therapy and photon therapy for early-stage non-small cell lung cancer: a meta-analysis - Junyi He; Yingxin Liu; Xiaojing Zhang; Butuo Li; Linlin Yang; Haohua Wang; Shijiang Wang; Jinming Yu; Linlin Wang (BMC, 2024)
Abstract The use of proton therapy (PT) in early-stage non-small cell lung cancer (ES-NSCLC) remains controversial, with insufficient evidence to determine its superiority over photon therapy (XRT). We conducted a systematic review of PT trials in ES-NSCLC, analyzing dosimetry, efficacy, and safety across to inform clinical decision-making. Our study showed that PT reduced lung and heart dosimetric parameters compared to XRT, with significant differences in lung V5, lung V10 and mean heart dose (MHD). In terms of efficacy, there were no significant differences in 1-year OS, 3-year OS and 3-year PFS between PT and XRT. For toxicity, no significant difference was observed in treatment-related adverse events (TRAEs) and radiation pneumonitis (RP). Single-arm analysis of PT found that V5, V10, V20 of lung and heart V5 were 13.4%, 11.3%, 7.9% and 0.7%, respectively. The mean lung dose and MHD were 4.15 Gy and 0.17 Gy, respectively. The single-arm pooled 1-, 2-, 3- and 5-year OS rates for PT were 95.3%, 82.5%, 81.3% and 69.3%, respectively. PFS rate and local control rate at 3 years were 68.1% and 91.2%, respectively. The rates of TRAEs of grade ≥ 3 and grade ≥ 2 were 2.8% and 19.8%, respectively. The grade ≥ 2 RP occurred at a rate of 8.7%. In conclusion, PT had acceptable efficacy and safety, and was better at protecting organs at risk than XRT in ES-NSCLC. However, the survival and safety benefit of PT was not significant compared to XRT.